Utilization of textured vegetable protein and agar in a low-fat high-fiber hamburger formulation - De Leon, Sharon B.; Dumelod, Benelyn Domingo (2000., 2000)
ABSTRACT The study aimed to utilize TVP and agar in a low-fat, high-fiber hamburger formulation. Phase I dealt with the selection of the most acceptable hamburger formulation. Three hamburger formulations were prepared and subjected to sensory evaluation. Kramer's Rank Sum Test (α=0.05) was applied to analyze results. Phase II involved the determination of the optimum level of TVP substitution and agar incorporation in the hamburger formulation. Sixteen hamburger samples with varying levels of TVP and agar were prepared and evaluated by 12 semi-trained panelists. Based on the two-way Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT)results, the formulation with 20% TVP and 1% agar was determined as the most acceptable formulation. In Phase III, three bench scale production runs were done and samples from each production run were evaluated. Based on ANOVA results at α=0.05, the samples were not significantly different thus formulation and process are reproducible. Phase IV focused on the physico-chemical and cost analyses of the control and the TVP-substituted and agar-incorporated hamburger formulation has a moisture content of 42.40%, crude fat content of 20.70%, crude protein content of 27.35%, available carbohydrate content of 7.50%, crude fiber content of 0.53% and ash content of 4.25%. Its water acidity is 0.40 while its pH is 5.50. The cost of a 50.0-gram TVP substituted and agar-incorporated hamburger patty is PhP 7.00 while in all-beef burger patty of the same weight costs PhP 7.20.
Thesis (BSFT)-- University of the Philippines Diliman
Keywords: Textured vegetable protein; Cookery (Beef).